Beyond sincerity and pretense: role-playing and unstructured self in the Zhuangzi. Issue 1 (2nd January 2016) - Machek, David
ABSTRACT: This article engages with a recent view that the Daoist Classic Zhuangzi advances an alternative to the Confucian role-ethics. According to this view, Zhuangzi opposes the Confucian idea that we should play our social roles with sincerity and instead argues that we should take the liberty to detach ourselves from the roles we play and 'pretend' them. It is argued in this article that Zhuangzi's ideal of role-playing is based neither on sincerity nor on pretense. Instead, it is akin to the excellence of theatre actors when they enact a role: they are able, for a limited time, to restructure their personality into a particular role, but de-structure it again when the performance is over. The prerequisite for this ability is to keep one's self fundamentally unstructured, or, as Zhuangzi puts it, 'empty' ( xu 虛). This reading of Zhuangzian role-playing provides a fresh perspectives on 'playing' or 'rambling' ( you 遊) as the central philosophical concept in the Zhuangzi .